'Art Happens not in Isolation, But in Community': The Collective Literacies of Media Fandom. Issue 1 (10th December 2019) - Jenkins, Henry
When the Archive of Our Own (AO3) received a prestigious Hugo Award from the World Science Fiction Convention in Dublin the summer of 2019, this moment represented a recognition by the literary science fiction community of an alternative model of authorship – one which operates outside the publishing world or academia, one where authorship is collective rather than individual, and one where artworks are appropriative and transformative rather than "original." Using this occasion as my starting point, I will discuss here the ways that the literacies associated with fandom may be understood as illustrative of the new forms of expression that have taken shape in a networked era.